Integrasi Metode Dalcroze dalam Pembelajaran Biola: Evaluasi Pedagogis dan Praktis - Richard Jr. Kapoyos; Laura Megawaty Manalu (Program Studi Pendidikan Musik FBS UNP, 2024)
Purpose: This research aims to determine the effectiveness of using the Dalcroze eurhythmics method in violin teaching. Several cases indicate that many students have difficulty understanding the material in violin courses due to the ineffective teaching methods used by lecturers during the learning process. Method: This research employs a qualitative approach with a descriptive method, which intends to create descriptions of situations or events. Based on data sources, this type of research falls into the category of field research. Results and Discussion: The results and discussion indicate that the Dalcroze method proposed by Jacques Dalcroze requires good musical skills from the educator. Additionally, educators are required to be active and creative in delivering music lessons. As instructors, educators should not only introduce various musical instruments that can be used to play popular songs. Conclusion: Educators should be able to train students in solfeggio to enhance their auditory sensitivity through ear training, thus becoming skilled in reading notes, sight reading, and understanding the upward and downward movements and the length and shortness of each notation beat.